Analysis of the inhibition of thermal degradation of molten polycarbonate at tool steel interfaces by thin TiAlN coatings - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; to Baben, M.; Rueß, H.; Schneider, J.M.; Grundmeier, G. (Polymer Degradation and Stability)

Analysis of dispersive interactions at polymer/TiAlN interfaces by means of dynamic force spectroscopy - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Gebhard, M.; Devi, A.; Grundmeier, Guido (Physical Chemistry Chemical Physics)
Dispersion forces due to polarizable subsurface layers govern TiAlN/polymer interactions and decrease by 50% when oxidizing TiAlN to form TiAlO.

Adhesion of plasma-deposited silicon oxide barrier layers on PDMS containing polypropylene - Hoppe, C.; Mitschker, F.; Awakowicz, P.; Kirchheim, D.; Dahlmann, R.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Coatings Technology)

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)

Plasma-Enhanced Chemical Vapor Deposition (PE-CVD) yields better Hydrolytical Stability of Biocompatible SiOx Thin Films on Implant Alumina Ceramics compared to Rapid Thermal Evaporation Physical Vapor Deposition (PVD) - Böke, Frederik; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido; Fischer, Horst (ACS Applied Materials & Interfaces)

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion - Oertel, Jana; Keller, Adrian; Prinz, Julia; Schreiber, Benjamin; Hübner, René; Kerbusch, Jochen; Bald, Ilko; Fahmy, Karim (Scientific Reports)

Structural stability of DNA origami nanostructures in the presence of chaotropic agents - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Nanoscale)

Adsorption and adhesion studies of PdSn-nanoparticles on protonated amine and carboxylic acid-terminated surfaces - Mosebach, Bastian; Bayer, Frank Markus; Fels, Carl-Christian; Voigt, Markus; Oezkaya, Berkem; Pomorska, Agata; Torun, Boray; Keller, Adrian; Grundmeier, Guido (Surface and Interface Analysis)

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.